Morgane Cadieu. On Both Sides of the Tracks: Social Mobility in Contemporary French Literature. The University of Chicago Press, 2024. - André Pettman (Studies in 20th & 21st Century Literature, 2025)
Review of Morgane Cadieu. On Both Sides of the Tracks: Social Mobility in Contemporary French Literature. The University of Chicago Press, 2024. 362 pp.
Keywords: French and Francophone Studies; social class; social mobility